Assessment of teacher professional development as a change agent for the mining and metallurgical industries - Nichols, Dianne Kay (Curtin University, 2015)
Science educators attended professional development programs about the mining and mineral processing industries. A mixed method primary data collection approach was used to investigate changes in attitude to the mining and mineral process industry and their ability to apply content knowledge application about the mining and mineral processing industries to their curriculum documents. The findings showed that after the professional development programs the science educators where able to make positive shifts in both areas.